Diametrical effects of glucose levels on microvascular permeability of peripheral nerves in patients with type 2 Diabetes with and without diabetic neuropathy - Mooshage, Christoph; Schimpfle, Lukas; Kender, Zoltán; Szendrödi, Julia; Heiland, Sabine; Nawroth, Peter Paul; Bendszus, Martin; Kopf, Stefan; Kurz, Felix T.; Jende, Johann (Diabetes, 2023)
Clinical studies investigating the benefit of glucose control on the progression of diabetic neuropathy (DN) have come to controversial results in patients with type 2 diabetes (T2D). This study aimed to assess associations of HbA1c levels with parameters of nerve perfusion in patients with T2D with and without DN using dynamic contrast-enhanced magnetic resonance neurography (DCE-MRN) at 3 Tesla. A total of 58 patients with T2D (20 with DN and 38 without DN) took part in this cross-sectional single-center study. Groups were matched for age, BMI, HbA1c, duration of T2D, and renal function. All patients underwent DCE-MRN with subsequent electrophysiologic and serologic testing. The extended Tofts model was used to quantify the sciatic nerve’s microvascular permeability (Ktrans), volume fraction of the extracapillary extracellular space, and volume fraction of the plasma space. As a main result, we found that Ktrans correlated positively with HbA1c in patients with DN, while a negative correlation between the two parameters was found in patients without DN. Our results indicate that the effect of glucose control on the capillary permeability of peripheral nerves differs between patients with T2D with and without DN.
November 03 2022
Gesehen am 03.07.2023